Efisiensi Kumbang Menochilus sexmaculatus sebagai Predator Kutu Kebul pada Tanaman Cabai (Capsicum annum L.) - Muhhammad Nur Kholis; Karisa Kinanti Khatimah; Yunia Shinta Bella; Khoirul Imam Tantowi; Muhammad Apriadi; Rionaldi Nainggolan; Arsi Arsi (Seminar Nasional Lahan Suboptimal, 2021)
Kholis MN. Khatimah KK, Bella YS, Tantowi KI, Apriadi M, Nainggolan R, Arsi A. 2021. Efficiency of the beetle menochilus sexmaculatus as natural enemy of whitefly on  chili plants (Capsicum annum L.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 134-141. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Whitefly is a serious pest on chili (Capsicum annuum L.) that can cause direct damage to plants or be a carrier of viral diseases. Whitefly is an important pest found in various horticultural crops including chili..This article to knowing the role of Menochilus sexmaculatus as a predator of the whitefly pest (Bemisia tabaci) on chili plants. This article was compiled from various literature studies Menochilus sexmaculatus is a whitefly predator, its presence as a predator on agricultural land is considered to have a high ability to adapt to the environment and has a greater ability to scatter than other types of natural enemies. The predatory species Menochilus sexmaculatus worked well in controlling whitefly populations on chili plants. Menochilus sexmaculatus can prey on 200-400 whitefly nymphs per day. Suppression of whitefly populations is very useful in suppressing the occurrence of jaundice by the gemini virus. The conclusion use of Menochilus sexmaculatus as a predator has been proven to reduce whitefly populations, especially during the rainy season.